Política pública de educação e Proposta Curricular do Estado de São Paulo: percepções sobre a eficácia - Capalbo, Roberta Braga (2010)
This research aims to examine the interpretation and application of a public educational policy in effect-Curricular Proposal of the State of São Paulo -, focusing on their arrival and experiential practice in the curriculum of schools in the Public School Network. As the object of study we have documents that make up the Curriculum Proposal, critical analysis published by the Association of Teacher Education Journal of São Paulo (APEOESP), criticism from some experts and opinion of teachers on the network. For their achievement are being developed, concomitantly, three types of research: theoretical research, which will assist in building concepts with foundation in Paulo Freire, Pedro Demo, Mário Sérgio Cortella and Enrique Dussel; empirical research with the collection Data from reality through expressions of opinions of academics, experts and professors from the network and actual occupants of function activity (OFA), and historical research, aiming to describe and analyze the changes undergone by the legal education over the government Serra of São Paulo, focusing on the changes that are still under implementation. The intention with this proposed study to verify the level of effectiveness of educational public policies with respect to their translation into reality from the perspective of teachers